Supporting the Contribution of Higher Education Institutions to Regional Development Peer Review Report: Atlantic Canada - Garlick, S; Davies, G; Polese, M; Kitagawa, F (Organisation for Economic Cooperation and Development (OECD), 2006)
Atlantic Canada comprises the three Maritime Provinces, Nova Scotia, Prince Edward Island and New Brunswick along with Newfoundland and Labrador. The size, demography, geography and diversity of Atlantic Canada, its juxtaposition with the rest of Canada and North America, and the presence of multiple actors and spheres of government make it a complex geography for regional development purposes. In order to reduce the brain drain, to deliver the enterprising human capital needs of the region’s economic base and to assist with a number of productivity and social equity benefits the OECD Peer Review Team recommends conjoint action and mobilising the universities and community colleges for the region.